Dual pH- and temperature-responsive protein nanoparticles. (August 2015) - Matsumoto, Nicholas M.; Buchman, George W.; Rome, Leonard H.; Maynard, Heather D.
Abstract : Graphical abstract: Highlights: We describe dually-responsive vault-polymer biohybrid nanoparticles. Poly( N -isopropylacrylamide- co -acrylic acid) was conjugated to human major vault protein. The smart vault reversibly aggregates depending on pH and temperature. Abstract: Multiply responsive protein nanoparticles are interesting for a variety of applications. Herein, we describe the synthesis of a vault nanoparticle that responds to both temperature and pH. Specifically, poly( N -isopropylacrylamide- co -acrylic acid) with a pyridyl disulfide end group was prepared by reversible addition-fragmentation chain transfer (RAFT) polymerization. The polymer had a lower critical solution temperature (LCST) of 31.9 °C at pH 5, 44.0 °C at pH 6 and above 60 °C at pH 7. The polymer was conjugated to human major vault protein (hMVP), and the resulting nanoparticle was analyzed by UV–Vis, dynamic light scattering (DLS) and electron microscopy. The data demonstrated that the poly( N -isopropylacrylamide- co -acrylic acid)-vault conjugate did not respond to temperatures below 60 °C at pH 7, while the nanoparticles reversibly aggregated at pH 6. Furthermore, it was shown that the vault nanoparticle structure remained intact for at least three heat and cooling cycles. Thus, these dually responsive nanoparticles may serve as a platform for drug delivery and other applications.